Survival of adolescents with cancer treated at pediatric versus adult oncology treatment centers in France. Issue 5 (15th November 2016) - Desandes, Emmanuel; Brugieres, Laurence; Laurence, Valérie; Berger, Claire; Kanold, Justyna; Tron, Isabelle; Clavel, Jacqueline; Lacour, Brigitte
Abstract: Background: In France, although children aged less than 15 years with cancer are usually referred to pediatric oncology centers, adolescents may be treated at pediatric or adult oncology centers. The objective was to compare survival according to their site of treatment. Procedure: Using population‐based registration, 15‐ to 19‐year‐old patients diagnosed with cancer in 2006 or 2007 and living in six French regions (accounting for 41% of the French population) were included. Results: Of the 594 patients included, 33% of the French adolescents were treated at a pediatric oncology center. Compared with those treated at a pediatric center, adolescents treated at an adult center were older, were more likely to have carcinoma and germ‐cell tumor, had a longer time to diagnosis, and were less likely to be enrolled in a clinical trial. In addition, the decisions for their management were less likely to be taken in the context of multidisciplinary team meetings. In multivariate analysis, adolescent patients treated at a pediatric center did not have significantly different overall survival (OS) compared with those treated at an adult center (5‐year OS: 84.1% [95% confidence interval: 78.6–90.0] versus 87.7% [95% confidence interval: 84.2–91.3]; P = 0.25). Conclusions: The outcomes of French adolescents with cancer have begun to improve, with 81.2% survival in 2006–2007, with no difference between the types of treatment center. However, for this unique group of diseases, survival is not the unique endpoint. In order to ensure good quality of life after cancer, management of those patients requires specific approaches, designed to reduce the late effects of cancer treatment and improve supportive care.